2000
DOI: 10.1159/000017507
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Assessment of Acne Vulgaris Patients

Abstract: Background: The relationship between acne and psychological well-being has been a subject of controversy. There is paucity of data on the role of anger in acne vulgaris. The present study was designed to delineate the relevant psychometric characteristics of acne vulgaris and specifically to shed light on the role of anger in acne vulgaris. Patients and Methods: 31 acne vulgaris patients and 25 controls with healthy skins were recruited in the study. The subjects were assessed by Beck Depression Inventory, Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
10
1
3
Order By: Relevance
“…We did not find any difference for depression between genders. This was unlike in few earlier studies where women were found to be having more severe depression than men, 6, 9 but a recent study by Golchai et al have not found any difference between genders similar to ours. 11 Our results show that depression was significantly higher in inflammatory acne group compared to noninflammatory acne group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find any difference for depression between genders. This was unlike in few earlier studies where women were found to be having more severe depression than men, 6, 9 but a recent study by Golchai et al have not found any difference between genders similar to ours. 11 Our results show that depression was significantly higher in inflammatory acne group compared to noninflammatory acne group.…”
Section: Discussioncontrasting
confidence: 99%
“…4 Depression have been found to be more prevalent among acne patients than controls. [5][6][7] Even suicidal ideation was found in 6-7% of acne patients 8 It has been shown that females are more vulnerable than males to the negative psychological effects of acne. 9 Recently Durai and Nair 10 in 2015 found acne vulgaris to affect the quality of life of individuals in South India.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that acne patients scored significantly higher than other medical out-patients on anxiety and depression, indicating that the skin disorder acne has a profound psychological impact on patients' psychological wellbeing as assessed pre-treatment. Similarly, a study by Sayar et al [2000] reported that acne patients had significantly higher depression scores than controls with healthy skin. Further examination of scores obtained on the HADS revealed that both anxiety and depression scores for acne patients decreased significantly over treatment time, although the positive affectivity scale of the PANAS was not significantly different than normative population data, and scores obtained from the Rosenberg Index of Self-esteem indicated that acne patients displayed higher self-esteem than the norm (low scores indicate high self-esteem).…”
Section: Discussionmentioning
confidence: 86%
“…However, when acne patients are compared to other skin patients using a depression test inventory, acne patients are found to be almost equally depressive as hospitalized psoriasis patients [Gupta and Gupta, 1998]. Sayar et al [2000] compared 31 acne patients with 25 skinhealthy controls and observed increased trait anxiety and depression levels in the acne patients. The authors conclude that the high level of trait anxiety may be due to the longstanding disability caused by acne in social circumstances.…”
Section: (Test-) Psychological Abnormalities In Acne Patientsmentioning
confidence: 99%